2003
DOI: 10.1890/02-0598
|View full text |Cite
|
Sign up to set email alerts
|

Local vs. Landscape Controls on Plant Species Richness in Beaver Meadows

Abstract: There is considerable interest in determining whether the species richness of communities is determined by forces controlling dispersal into patches that operate at the landscape scale, or forces controlling persistence that act at the local scale. Understanding the relative importance of these two classes of factors in controlling within‐patch species richness is particularly important when patches are created via ecosystem engineering. In such cases, factors affecting the population dynamics or behavior of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
60
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(64 citation statements)
references
References 42 publications
3
60
0
1
Order By: Relevance
“…Two disparate perspectives on this issue, dis persal assembly and niche assembly, have recently been combined in metacommunity models predicting the compo sitions of local communities (Cornell and Lawton 1992;Holyoak et al 2005;Leibold et al 2004). Comparative and experimental studies assessing the relative contributions of niche-and dispersal-assembly processes have typically found that both sets of processes impact community struc ture (Chase 2003;Cottenie et al 2001;Cottenie and De Meester 2004;Friedenberg 2003;Kneitel and Miller 2003;Shurin 2001;Tilman 1997;Tofts and Silvertown 2002;Wright et al 2003). However, these empirical studies have rarely been conducted in the context of the patterns of spe cies distributions across natural habitat gradients, despite the potential for this approach to provide useful tests of metacommunity models (but see Urban 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Two disparate perspectives on this issue, dis persal assembly and niche assembly, have recently been combined in metacommunity models predicting the compo sitions of local communities (Cornell and Lawton 1992;Holyoak et al 2005;Leibold et al 2004). Comparative and experimental studies assessing the relative contributions of niche-and dispersal-assembly processes have typically found that both sets of processes impact community struc ture (Chase 2003;Cottenie et al 2001;Cottenie and De Meester 2004;Friedenberg 2003;Kneitel and Miller 2003;Shurin 2001;Tilman 1997;Tofts and Silvertown 2002;Wright et al 2003). However, these empirical studies have rarely been conducted in the context of the patterns of spe cies distributions across natural habitat gradients, despite the potential for this approach to provide useful tests of metacommunity models (but see Urban 2004).…”
Section: Introductionmentioning
confidence: 99%
“…For example, after being nearly extirpated by European colonists, North American beavers (Castor canadensis) are now thriving over much of their historical range and fundamentally modifying hydrologic regimes (Naiman et al 1988), plant and animal communities (Martinsen et al 1998;Wright et al 2002Wright et al , 2003Pollock et al 2003), and elemental cycling (Naiman et al 1994). Beavers are best known as ecosystem engineers (sensu Jones et al 1994) with the propensity to alter landscapes by felling trees, constructing dams, and digging canals (MullerSchwarze and Sun 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Beavers, however, eat both woody and non-woody plants, often spending the majority of their time foraging for herbaceous plants, particularly in the summer (Tevis 1950;Jenkins 1980;Svendsen 1980;Doucet and Fryxell 1993). Despite these well-known foraging patterns, beaver impacts on herbaceous aquatic plant communities are generally attributed to the indirect eVects of ecosystem engineering, including changes in water depth, sediment composition, and Xood plain geomorphology (Naiman et al 1988;Ray et al 2001;Wright et al 2002Wright et al , 2003. Few studies have experimentally examined the direct eVects of herbivory by this common and widespread aquatic herbivore.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, these lines will have to integrate the main determinant ecological (phytogeographic) factors as well as local factors that determine differences in the distribution of plant communities (Stephenson, 1990;Huston, 1999;Wright et al, 2003;Zelený et al, 2010;Bui, 2013;Costa et al, 2013;Dorman et al, 2013;Laliberté et al, 2013;Moeslund et al, 2013).…”
Section: Application To the Universe Of Small Islandsmentioning
confidence: 99%